The Role of Financial Performance in Corporate Environmental Expenditure Moderated by Independent Commissioners - Pratama, Muhammad Rahmadi; Heniwati, Elok; Kurniawan, Rudy (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
This study analyzes the influence of profitability, liquidity, and leverage on environmental costs, moderated by independent commissioners. The sample consists of 126 mining and palm oil companies listed on the Indonesia Stock Exchange for 2021–2023, totaling 378 observations. This Study were analyzed using panel data regression method.  the results show that profitability significantly increases environmental costs, while liquidity has a significant negative effect and leverage is insignificant. Independent commissioners do not directly affect environmental costs but strengthen the link between liquidity and environmental spending. These findings suggest that financial performance shapes environmental commitments in different ways, whereas the supervisory role of independent commissioners remains limited. Theoretically, this study reinforces stakeholder theory by confirming that profits extend beyond shareholders to social–environmental needs and enriches environmental accounting literature by revealing liquidity constraints on sustainability. The implications are relevant for companies, boards, and regulators in enhancing sustainability governance.